Peran Guru dalam Mendidik Anak Usia Dasar (Studi Kasus: Sekolah Dasar Islam Plus YLPI Pekanbaru) - Wulandari, Isra; Salsabila; Zahara, Nabila; Salsa Billa, Adinda; Mustika, Dea (Innovative: Journal Of Social Science Research, 2025)
Teachers are an important part of the teaching and learning process. An educator contributes to the formation of human resources in the field of development. According to experts, a professional teacher is anyone who is responsible for the education of their students, either individually or classically, in schools or outside of school. As an important part of the implementation of educational programs in schools, teachers have a very important responsibility to achieve educational goals. In their work as teachers, they are responsible for teaching, guiding, training, advising, changing, being examples and role models, having personality, researching, encouraging creativity, generating views, doing routine work, transporting stories, being actors, emancipators, preserving, as culminators, and conducting evaluations. To develop education, teachers must instill values, build character, build learning centers, offer assistance and encouragement, supervise and coach, discipline students, and be role models for their environment. The purpose of this study was to determine the role of teachers in educating elementary school children. Educating is the process of encouraging children to develop and develop until they become physically and spiritually mature. Parents play an important role as educators of children, while teachers only have time to teach. In this study, SD Islam plus YLPI Pekanbaru used a case study approach. Data were collected through interviews and observations.